Europe and migration (Academic Journal of Internal Affairs, 2019)
Migration became part of our every day’s life, the news about it you can see on television, hear on radio, read in newspapers and in online media. Despite that – and this is confirmed by my own research, too -we have not enough reliable information available. Even therefore is a stopgap collection of essays the book Europe and migration edited by the Scientific Research Place of the Hungarian Defence Force and published by Zrinyi Kiadó. The editors of the book, i.e. János Besenyő, tutor at Safety Science Doctoral School of the Óbuda University, Péter Miletics, associate of the research place and Balázs Orbán, former director-general of the Századvég Migration Research Institute are accepted experts of the topic. It is to highlight that the book examines migration not only in focus of an only scientific field but in a multidisciplinary and in an integrated transdisciplinary attitude as usual on the field of political science.
Keywords: book review; Europe; migration